Weaning Breast Milk Age As Factor Cause Of Nutritional Status Of Children Aged 0-2 Years In Jeli Posyandu Karangrejo Village District Tulungagung Year 2019 - Farasari, Poppy (Journal of Global Research in Public Health, 2019)
Toddlers are groups of children who are in the process of growth and development that is unique, meaning that it has a pattern of growth and physical development can determine the nutritional status of children. Nutritional status is a state of balance between intake and nutrient requirements needed by the body for growth and development, especially for children under five, which could be affected by weaning is a process cessation of lactation gradually or all at once. Age weaning is done too early can have an impact on the nutritional status of children <1 year. This study aims to determine the age of weaning breastfeeding relationship with ststus nutrition of children aged 0-2 years in Poyandu Jelly Village, District Karangrejo, Tulungagung in 2019. The study design was analytical research retrospektive approach. The population is all the mothers who have children aged 0-2 years and had weaned him. Subjects were toddlers usi 0-2 years who had been weaned by his mother in Posyandu Jellies, District Karangrejo, Tulungagung in 2019 by 30 respondents with accidental sampling technique. The collection of data by using sheet kuosioner then analyzed using Spearman Rho. The results showed that the weaned child aged 13-24 months gained as much as 8 normal nutritional status of children (72.7%) and the weaned child aged 0-6 months less nutritional status of 8 children (100%), the results of analysis p value = 0,000 with α = 0.05 means there is a relationship of age of weaning breastfeeding and nutritional status of children aged 0-2 years in Poyandu jelly Village, District Karangrejo, Tulungagung in 2019. With the results of these studies, need to increase information about the importance of proper breastfeeding weaning age that had no impact on the nutritional status of children in the IHC.